Multiplex immunofluorescence assessment of macrophages and IL-23R in inflammatory and malignant diseases of the oral mucosa: a pilot study - Trumet, Leah; Grötsch, Bettina; Agaimy, Abbas; Galler, Kerstin; Geppert, Carol; Winter, Linus; Ries, Jutta; Kesting, Marco; Weber, Manuel (Frontiers in Immunology, 2025)
BackgroundImmune cells play a major role in the development and progression of inflammatory and malignant diseases of the oral mucosa. There is growing evidence that immune cells contribute to oral cancer progression and metastases. Inflammatory carcinogenesis is believed to be relevant for oral Lichen Planus as well as for oral Leukoplakia. In addition, there is growing evidence that periodontitis might also be linked to oral cancer development. Yet there is no analysis available comparing the immune cell composition in these different inflammatory and malignant neoplastic diseases. A better understanding of similarities and differences of the diseases could eventually also pave the way for the use of immunotherapy in non-malignant diseases.MethodsIn the current pilot study, a tissue microarray (TMA) was created of a total of 29 patients with periodontitis (PD, n=4), oral Leukoplakia (OL, n=4), oral Lichen Planus (OLP, n=4), oral squamous cell cancer without lymphatic metastases (OSCC N0, n=5), or with lymphatic metastases (OSCC N+, n=4), OSCC biopsies prior to and resection specimens after anti-PD1 immunotherapy (IT) (each n=3) as well as healthy control gingiva (n=5). In each patient two tissue samples were analyzed. The TMA was stained with a 4X multiplex immunofluorescent staining for IL-23R, CD68, CD11c, and CD163. Samples were digitalized and an AI-based cell counting was performed. Statistical analysis was performed using the Mann-Whitney U test.ResultsIL-23R expression, macrophage infiltration as well as M2 polarization in OL and OLP were significantly higher compared to controls. OLP showed a significantly higher M2 infiltration and polarization than OL. PD showed a trend for increased macrophage infiltration compared to controls without significance. N+ OSCC showed a significantly increased macrophage infiltration compared to N0 cases. In response to anti-PD1 IT, CD11c and CD163 infiltration was significantly increased. Most IL-23R positive cells co-expressed macrophage markers.ConclusionA TMA in combination with 4-plex immunofluorescence is suitable for immune cell characterization in different oral diseases. Macrophage infiltration and polarization in precursor lesions seems to be associated with OSCC development as well as metastatic spread. IL-23 pathway inhibition might be a potential target for oral Lichen and Leukoplakia.